Underpinning And Micropiling To A Four Storey Apartment Building In Hamilton, Scotland - Clifford J. Wren (Deep Foundations Institute, 2008)
A geotechnical foundation solution was required to halt and prevent further structural distress suffered by a residential four storey apartment building in Hamilton, Scotland. Residents of the ten year old building started to notice cracking and signs of distress approximately one year after moving into the property. A detailed intrusive inspection of the structure revealed that the building was moving and had suffered significant settlement and structural distress at the shared party wall between it and an adjoining building. Roger Bullivant Limited (RBL) was appointed Principal Contractor to carry out an agreed remedial works contract which included a complete structural ?strip-out? of the ground floor, underpinning, contiguous bored pile retaining wall and reinstatement. The paper describes how a proprietary pile and needle beam underpinning system was used to prevent further differential movement and provide a new secure foundation for the residential building. The case study illustrates how a flexible problem solving approach can be applied to a difficult and sensitive geotechnical project.